2019
DOI: 10.1093/pm/pnz094
|View full text |Cite|
|
Sign up to set email alerts
|

“My Surgical Success”: Effect of a Digital Behavioral Pain Medicine Intervention on Time to Opioid Cessation After Breast Cancer Surgery—A Pilot Randomized Controlled Clinical Trial

Abstract: Objective This study aims to assess the feasibility of digital perioperative behavioral pain medicine intervention in breast cancer surgery and evaluate its impact on pain catastrophizing, pain, and opioid cessation after surgery. Design and Setting A randomized controlled clinical trial was conducted at Stanford University (Palo Alto, CA, USA) comparing a digital behavioral pain medicine intervention (“My Surgical Success” [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 39 publications
2
74
0
2
Order By: Relevance
“…Digital therapeutics offer independent, home-based, on-demand access to behavioral treatment for acute and chronic pain. For instance, a brief, web-based, 90-min, skilled-based pain treatment was shown to reduce postsurgical opioid use in women who underwent surgery for breast cancer [ 14 ]. For chronic pain, digital multisession interventions have been shown to be effective [ 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digital therapeutics offer independent, home-based, on-demand access to behavioral treatment for acute and chronic pain. For instance, a brief, web-based, 90-min, skilled-based pain treatment was shown to reduce postsurgical opioid use in women who underwent surgery for breast cancer [ 14 ]. For chronic pain, digital multisession interventions have been shown to be effective [ 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other digital interventions exist that support PROM feedback for individuals with symptomatic cancer [10,12,[31][32][33]. Some provide Web-based pain management advice [34], deliver psychological therapies or support for individuals with cancer pain [35,36] or focus on specific situations such as post-surgical pain management [37]. Most psychoeducational and PROM feedback interventions can achieve small reductions in pain intensity, and it is difficult to know which components are effective [21].…”
Section: Context With Other Literaturementioning
confidence: 99%
“…To date, the US lacks scalable behavioral medicine for pain thereby underscoring the need for solutions that are accessible, low-cost, and lowburden. Evidence-based, skills-based behavioral medicine for pain has been shown to reduce pain-specific distress [4,5], pain intensity [6], pain bothersomeness [7], improve response to pain treatments [8], and reduce opioid use among perioperative patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…A single-session, 2-h skills-based pain management class ("Empowered Relief" (ER)) was shown to reduce pain-specific distress and improve self-regulation at 4week follow-up in a cohort of 57 mixed-etiology chronic pain patients receiving treatment at a tertiary referral, multidisciplinary chronic pain clinic [4]. A recent randomized controlled trial showed that a digital version of the class, adapted to the perioperative setting, effectively enhanced time to opioid cessation after breast cancer surgery compared to a digital health education control ("My Surgical Success") [9]. Importantly, neither "Empowered Relief" nor "My Surgical Success" direct patients to use less opioid medication.…”
Section: Introductionmentioning
confidence: 99%